Trends and challenges of metadata creation in web archiving projects - Blanco-Rivera, Joel Antonio (2022)
This paper aims to identify practices and challenges related to metadata management in web archiving projects. An analysis of literature on metadata in web archives published since 2013 is carried out, with particular attention to identify studies on these practices in archives and libraries. These findings point to the need to provide further contextualization on the shaping of a web archive or collection, as well as the importance of building bridges between library and archival practices. In addition, to deepen on the importance of metadata in web archiving projects, the conformation and cataloging of the #RickyRenuncia Web Collection, which is part of the RickyRenuncia Project, a collaborative and voluntary initiative to document the protests that led to the resignation of the governor of Puerto Rico in July 2019, is presented as a case study. By way of conclusion, it argues about the need to learn more about web archiving practices in Latin America and the Caribbean, and about the possibility of establishing collaborative networks aimed at strengthening the preservation of web content in the region.